2015
DOI: 10.5120/19544-1409
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for Optimum Sizing of a Photovoltaic Water Pumping System

Abstract: A sizing algorithm for a photovoltaic water pumping installation composed of photovoltaic panels, battery' bank, DC/AC converters and a water pump is presented. Considering criteria related to the battery' bank safe operation, fulfilling the water volume needed by the crops and ensuring a continuous operation of the pump, the algorithm decides the size of the installation' components. The installation' cost using the presented and the basic algorithms are compared. Obtained results confirm that the water deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Consequently, this research paper presents a continuation of previously published works by some of the authors [17,18], where a sizing algorithm for a PV-battery installation destined for water pumping is proposed and evaluated. In fact, using the drip-irrigation technique for tomatoes, the pumped water is used here to irrigate an agriculture land situated in Northern Tunisia (latitude: 36.39º; longitude: 9.6º) during the crops vegetative cycle, which is from March to July.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Consequently, this research paper presents a continuation of previously published works by some of the authors [17,18], where a sizing algorithm for a PV-battery installation destined for water pumping is proposed and evaluated. In fact, using the drip-irrigation technique for tomatoes, the pumped water is used here to irrigate an agriculture land situated in Northern Tunisia (latitude: 36.39º; longitude: 9.6º) during the crops vegetative cycle, which is from March to July.…”
Section: Introductionmentioning
confidence: 86%
“…Indeed, the oversized case results in high installation costs. Whereas for an undersized case, the installation is unable to supply the load with the needed energy [17][18], as well as the installation lifetime is short due to excessive use of the batteries. Thus, the system size must be carefully selected for each specific application and location [1,16].…”
Section: Introductionmentioning
confidence: 99%
“…This type of system is well suited to applications where a constant volume of water must be pumped daily from a water source to the application or storage of water, as it's well simply because it consists of a direct coupling between the photovoltaic generator and the pump, and it is intended for pumping time throughout the day. In this case, the system can store energy or water to store the excess energy generated on days when solar energy is above average, either by storing extra electricity generated in batteries [1], or by pumping extra water and storing it.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major issues facing solar irrigation systems is the seasonal demand pattern for crops and the diversity of solar power generation. To cope with this problem, several photovoltaic systems use batteries to accumulate the electrical energy produced by the photovoltaic system to match energy production and demand [1]. However, the batteries have several disadvantages because they are heavy, expensive, fragile, and require maintenance of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a sizing algorithm is proposed to decide on the sizing of the installation As a general conclusion, we have shown that our proposed algorithm is adequate for the determination of the optimum components' sizes for the photovoltaic irrigation installation. The results have been presented in [42] and [79].…”
Section: Resultsmentioning
confidence: 99%